2018
DOI: 10.1177/1076029618786588
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between PFA-Measured Aspirin Resistance, Platelet Count, Renal Function, and Angiotensin Receptor Blockers

Abstract: Aspirin resistance is used to describe patients who are undergoing aspirin therapy but fail for the inhibition of thromboxane biosynthesis in platelets. Although the true mechanism is unclear, drug-drug interaction remains a possible factor. The study aimed to determine whether there was association between aspirin resistance and the concomitant cardiovascular medication. Using the Platelet Function Analyzer-100 system, aspirin resistance was evaluated in aspirin-treated patients from the outpatient department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
2
1
Order By: Relevance
“…Contrary to our findings, it has been reported that patients with aspirin resistance have higher platelet count and that other concomitant common cardiovascular medications, such as angiotensin receptor blocker and calcium channel blocker, may contribute to the higher platelet count in aspirin-resistant patients. 22 Although diabetes, obesity, and high cholesterol have been reported to be associated with aspirin resistance before, we did not find any significant difference between aspirin-resistant and control groups; this could be attributed to clopidogrel treatment or PCI affecting aspirin resistance.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Contrary to our findings, it has been reported that patients with aspirin resistance have higher platelet count and that other concomitant common cardiovascular medications, such as angiotensin receptor blocker and calcium channel blocker, may contribute to the higher platelet count in aspirin-resistant patients. 22 Although diabetes, obesity, and high cholesterol have been reported to be associated with aspirin resistance before, we did not find any significant difference between aspirin-resistant and control groups; this could be attributed to clopidogrel treatment or PCI affecting aspirin resistance.…”
Section: Discussioncontrasting
confidence: 77%
“…Contrary to our findings, it has been reported that patients with aspirin resistance have higher platelet count and that other concomitant common cardiovascular medications, such as angiotensin receptor blocker and calcium channel blocker, may contribute to the higher platelet count in aspirin-resistant patients. 22 …”
Section: Discussionmentioning
confidence: 99%
“…AR was detected in 147 (17.7%) of 831 patients. They demonstrated that concomitant ARB treatment in aspirin-treated patients decreased the risk of AR [ 26 ]. Supporting the findings of this study, presence of HTN was negatively correlated with AUC in our study.…”
Section: Discussionmentioning
confidence: 99%